Perencanaan Sistem Drainase Kawasan Bandar Udara Arung Palakka Kabupaten Bone Sulawesi Selatan - Patunrangi, Muhammad Haekal; Yusuf, Andi Rumpang; Badrun, Burhanuddin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Drainage system planning is essential for the Arung Palakka Airport area in Bone Regency. The geographic conditions exhibit varied weather patterns and inconsistent rainfall, posing a risk of water accumulation that could disrupt airport operations and impact the surrounding environment negatively. Thus, effective drainage planning requires analyzing the layout systematically. This study adopts a quantitative approach in both data collection and analysis. The objective is to propose a drainage system for the Arung Palakka Airport area and determine the appropriate dimensions for the primary channel structure that align with the runoff volume in this area. Findings from this study conclude that the Type A drainage scheme channels runoff from the runway, taxiway, and apron areas, while a retention pond collects runoff from both Type A and nearby areas. Calculations show that the primary drainage channel dimensions include a freeboard height (w) of 22.5 cm, a base width (b) of 60 cm, and a wetted height (h) of 75 cm, ensuring adequate drainage capacity.